Fibrillar cellular fibronectin supports efficient platelet aggregation and procoagulant activity - Maurer, Eric; Schaff, Mathieu; Receveur, Nicolas; Bourdon, Catherine; Mercier, Luc; Nieswandt, Bernhard; Dubois, Christophe; Jandrot-Perrus, Martine; Goetz, Jacky G.; Lanza, François; Gachet, Christian; Mangin, Pierre H. (Thrombosis and Haemostasis, 2015)
The ability of cellular fibronectin, found in the vessel wall in a fibrillar conformation, to regulate platelet functions and trigger thrombus formation remains largely unknown. In this study, we evaluated how parietal cellular fibronectin can modulate platelet responses under flow conditions. A fibrillar network was formed by mechanically stretching immobilised dimeric cellular fibronectin. Perfusion of anticoagulated whole blood over this surface resulted in efficient platelet adhesion and thrombus growth. The initial steps of platelet adhesion and activation, as evidenced by filopodia extension and an increase in intracellular calcium levels (419 ± 29 nmol/l), were dependent on integrins α5β1 and αIIbβ3. Subsequent thrombus growth was mediated by these integrins together with the GPIb-V-IX complex, GPVI and Toll-like receptor 4. The involvement of Toll-like receptor 4 could be conveyed via its binding to the EDA region of cellular fibronectin. Upon thrombus formation, the platelets became procoagulant and generated fibrin as revealed by video-microscopy. This work provides evidence that fibrillar cellular fibronectin is a strong thrombogenic surface which supports efficient platelet adhesion, activation, aggregation and procoagulant activity through the interplay of a series of receptors including integrins α5β1 and αIIbβ3, the GPIb-V-IX complex, GPVI and Toll-like receptor 4.
Keywords: Platelets; arterial thrombosis; haemostasis; fibronectin